Contextualizing If You Wanna Switch Seats, We Could - Medeiros, Lucy; Stannard, Lilly; Salvatore, Joe (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
The Verbatim Performance Lab (VPL) at New York University’s Steinhardt School conducted a Research-based Theatre investigation entitled If You Wanna Switch Seats, We Could. The project involved secondary school students from across the US performing a section of the September 2020 presidential debate between Donald Trump and Joe Biden. The aim was to explore how perceptions change when the debate is performed by young people. The project used the ethnodramatic form of verbatim performance, where actors portray someone word for word and gesture for gesture and often of a different identity. The project culminated in a virtual public sharing of the filmed investigations, and offered students an opportunity to gain a better understanding of their place in the political landscape.